P320 6-Thioguanine nucleotide levels are associated with trough levels of infliximab and adalimumab in Inflammatory Bowel Disease patients on combination therapy: A retrospective multicentre study. (21st January 2022) - Yu, N; Tassone, D; Lee, T; Phan, S; Wu, D M; Tjahyadi, J; Dutt, K; Liou, H; Wang, L; Zhang, J; Basnayake, C; Wright, E; et al.
Abstract: Background: Thiopurine co-therapy with anti-tumour necrosis factor alpha (anti-TNFα) agents is associated with higher anti-TNFα drug levels and reduced immunogenicity in patients with Inflammatory Bowel Disease (IBD). However, the, 6-thioguanine nucleotide (6-TGN) threshold level required to confer this benefit remains unclear. We aimed to evaluate the relationship between serum, 6-TGN levels and trough levels of infliximab (IFX) and adalimumab (ADA) in IBD patients on combination therapy. Methods: We performed a retrospective multicentre study of IBD patients receiving combination anti-TNFα and thiopurine maintenance therapy, for at least, 3 months duration with stable doses for at least, 2 months. All, 6-TGN levels measured within, 3 months prior to or on the same date as IFX or ADA trough levels, between January, 2015 and August, 2021, were included. Undetectable 6-TGN levels (<5pmol/8x10 8 RBC) were excluded. Patient demographics, disease characteristics, treatment details, biochemical results, and endoscopy results were collected. Primary outcomes were IFX and ADA levels. Secondary outcomes were antibodies to IFX (ATI) or ADA (ATA). Spearman's rho was used to correlate, 6-TGN and anti-TNFα levels. The Mann-Whitney U test was used to compare anti-TNFα levels between, 6-TGN quartiles, and, 6-TGN levels between patients with and without detectable ATI. Results: 483 paired, 6-TGN and anti-TNFα levels (426 IFX, 57 ADA) from, 266 patients (217 IFX, 49 ADA) were included. The median, 6-TGN level was, 240pmol/8x10 8 RBC, median IFX level was, 6.55mcg/ml and median ADA level was, 7.60mcg/ml. There were significant positive correlations between, 6-TGN and IFX levels (rho, 0.147, p=0.003), and, 6-TGN and ADA levels (rho, 0.266, p=0.047). Figure, 1 shows median IFX levels stratified by, 6-TGN quartiles (Q1:, 0–156, Q2:, 157–237, Q3:, 238–331 and Q4: >331pmol/8x10 8 RBC). There was a significant difference in IFX levels between Q2 and Q3 (p=0.017), but not between Q1 and Q2 (p=0.232), or Q3 and Q4 (p=0.544). Figure, 2 shows median ADA levels stratified by, 6-TGN quartiles (Q1:, 0–183, Q2:, 184–252, Q3:, 253–352, Q4: >352pmol/8x10 8 RBC). ADA levels did not differ significantly between, 6-TGN quartiles., 6 patients had detectable ATI. Of these, 5 patients had, 6-TGN levels in Q1 and, 1 patient had a, 6-TGN level in Q2. Patients with ATI had significantly lower, 6-TGN levels compared to those without ATI (median, 6-TGN, 147 vs, 239.5pmol/8x10 8 RBC, p=0.017). No patients had detectable ATA. Conclusion: 6-TGN levels are associated with IFX and ADA trough levels. Target, 6-TGN levels in the lower end of the therapeutic range may be adequate to maintain anti-TNFα levels and prevent anti-drug antibodies in combination therapy.